DNA methylation processes in atheosclerotic plaque. (February 2019) - Aavik, Einari; Babu, Mohan; Ylä-Herttuala, Seppo
Abstract: Underlying mechanisms of cardiovascular diseases (CVD) have been investigated for over 100 years and novel molecular level mechanisms in the pathophysiology are still continuously being discovered. Genetic polymorphisms (SNPs = single nucleotide polymorphisms) have explained about one tenth of the CVD risk, but polymorphisms fail to account for gene-environment interactions i.e. explain the dynamics of epigenome modifications in CVD. Accumulating evidence suggests that epigenetic modifications are actively reshaping pathological processes (e.g. dedifferentiation of smooth muscle cells, accumulation of senescent cells) in CVD. Senescence of vascular cells in ageing arteries not only counteracts regenerative processes but also exacerbates atherogenesis. Epigenome modifications include changes in DNA methylation, histone code and expression of non-coding RNAs. DNA methylation is a major epigenetic regulator modulating cell-type specific gene expression in mural cells, but there is some controversy regarding how to interpret the role of DNA hyper- and hypomethylation in CVD pathology. DNA hypomethylation (loss of methyl cytosines) appears to predominate in atherosclerosis, while a few genes become more methylated (i.e. hypermethylated) as the disease progresses in medium-sized and large arteries. The actual time-course of atherosclerosis-linked changes in genomic DNA methylation is still poorly studied. This review highlights recent novel findings which link alterations in DNA methylation to atherogenesis and points out new potential approaches for novel treatments.